A role-play to explain cartel behavior: Discussing the oligopolistic market. (May 2016) - Correa, Manuel; García-Quero, Fernando; Ortega-Ortega, Marta
Highlights: We provide a practical and easy tool to teach about oligopolistic markets. Didactic resources (cards etc.) add dynamism, realism and enrich original experiments. In 45 min, 12–48 students act as a member country of OPEC. The role play can include new treatments to be used in several economics courses. Abstract: The objective of this article is to provide an innovative and dynamic technique to teach strategic behavior in one of the most characteristic traits of the oligopolistic market: the cartel, in particular the Organization of Petroleum Exporting Countries (OPEC) cartel. We propose a classroom game consisting of a role playing game with 12–48 students who act as if they were a member country of OPEC. The students have to decide petroleum production in barrels to achieve the maximum benefit, taking into account price changes depending on their behavior. The classroom game (40–45 min to run) can be extended to include different treatments for use in basic economics, intermediate or advanced microeconomics or other courses that examine strategic behavior and the importance of institutions in economic performance.